Manajemen Sumber Daya Manusia (SDM) dalam Meningkatkan Kualitas Program Dakwah di Masjid Raya Pematang Siantar - Rizky Primadani; Waizul Qarni (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2026)
Human resource management (HRM) plays a crucial role in improving the quality of da’wah programs in mosques. This study aims to analyze the implementation of HRM in managing da’wah programs at Masjid Raya Pematang Siantar, as well as to identify obstacles and solutions to improve the effectiveness of da’wah activities. The research used a qualitative approach with interview, observation, and documentation techniques. Informants consisted of mosque administrators, preachers (da’i), and active congregants. The results showed that HRM in the da’wah programs already has a fairly clear organizational structure, but several aspects still need improvement. The recruitment of preachers is still conducted informally without clear competency standards, and there are no specialized training programs for preachers. Congregational participation also remains fluctuating. Another weakness is the minimal use of technology in disseminating da’wah information, as promotion is still carried out conventionally without optimizing digital platforms. In addition, limited funding and the lack of professional management personnel are major challenges. Solutions that can be implemented include improving preacher recruitment and training systems, utilizing technology in da’wah dissemination, and optimizing financial management through effective fundraising strategies. With better HRM implementation, da’wah programs at Masjid Raya Pematang Siantar are expected to operate more professionally and provide broader positive impacts on society